PENGGUNAAN STRATEGI YANG MENYENANGKAN DENGAN HUMOR DALAM MENINGKATKAN MOTIVASI BELAJAR SISWA KELAS 3 AL ADLU - Muhammad Nur Abdullah; Muchtar Hasanuddin (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study examines the effectiveness of humor-based learning strategies in increasing learning motivation of grade 3 students. Qualitative methods were used to analyze the application of three main types of humor: visual (cartoons), narrative (funny stories), and interactive (games). Results showed significant improvements in students' motivation, participation, and memory retention. The main challenges include adaptation to Islamic values and learning time management. This study recommends the development of a teacher training module for optimizing the use of educational humor.